Social protection after the Arab Spring - Rafael Guerreiro Osorio; Fábio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
When countries in the Middle East and North Africa (MENA) achieved their independence, formal social protection schemes established by former colonial powers were, to varying degrees, assimilated or mimicked by the State, particularly pension systems for government and formal-sector workers. These systems, however, have proven to be highly subsidised and regressive in terms of income distribution in the face of large segments of the population engaged in the informal sector (or rural work), who have remained excluded from formal social protection unless eligible for some social assistance programmes, mostly with lower coverage and benefits. In fact, a significant share of the social expenditure with a social protection function in most of these countries was assigned to universal or quasi-universal subsidies of fuel and staple foods. [...]
Keywords: 330; Social protection; Arab Spring